A new sequential animal model for infection-related non-unions with segmental bone defect - Helbig, Lars; Gühring, Thorsten; Titze, Nadine; Nurjadi, Dennis; Sonntag, Robert; Armbruster, Jonas; Wildemann, Britt; Schmidmaier, Gerhard; Grützner, Paul Alfred; Freischmidt, Holger (BMC musculoskeletal disorders, 2020)
The treatment of fracture-related infections (FRI) is still a challenge for orthopedic surgeons. The prevalence of FRI is particularly high in open fractures with extensive soft-tissue damage. This study aimed to develop a new two-step animal model for non-unions with segmental bone defects, which could be used to evaluate new innovative bone substitutes to improve the therapeutic options in humans with FRI and bone defects.
Gesehen am 14.10.2020